Risk Factors and Prevention of Leptospirosis in Indonesia: A Review - Tanri Yunanto Widodo; Laura Zhevania Florenti Edison (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: Leptospirosis is a zoonotic disease that continues to pose a significant public health challenge in Indonesia. It is caused by Leptospira bacteria, which are transmitted to humans through contact with water or soil contaminated by the urine of infected animals, particularly rodents. Objective: This study aims to examine the risk factors associated with the transmission of leptospirosis and to identify effective prevention strategies based on previous research conducted in Indonesia. Method: A literature review approach was employed, analyzing various published studies that investigated leptospirosis in the Indonesian context. The reviewed studies included observational, case-control, and cross-sectional designs, focusing on risk factors and prevention efforts. Relevant scientific articles were retrieved from reputable databases and analyzed descriptively. Results: The review highlights that environmental conditions such as stagnant water, inadequate drainage systems, and poor sanitation are major contributors to the incidence of leptospirosis. These factors create favorable conditions for the proliferation of rodents and increase the risk of human exposure to contaminated environments. Conclusion: Effective prevention of leptospirosis requires a multidimensional approach involving health promotion, environmental sanitation improvements, and rodent control initiatives. Collaborative efforts between the health sector, environmental agencies, and community organizations are essential to reduce the incidence and impact of leptospirosis in Indonesia. Keywords: Leptospira, Leptospirosis, Environmental Sanitation, Public Health, Indonesia.